DG SANGINGA'S Conferment Ceremony - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
Highlights of the Conferment of Dr. Nteranya & Mrs. Charlotte Sanginga the 7th Director-General of IITA as Aare Afurugbin-ola of the source held on 11th of December, 2021.